2010
DOI: 10.1007/s13233-010-0611-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and physical properties of the biocomposite, cellulose diacetate/kenaf fiber sized with poly(vinyl alcohol)

Abstract: Cellulose diacetate (CDA)/kenaf fiber biocomposites were prepared using a melting process. In order to increase the fiber density and compatibilize the kenaf fiber with CDA, the fiber was sized with poly(vinyl alcohol)(PVA). The sized kenaf fiber was compounded with the plasticized CDA using a twin screw extruder, and the optimal processing conditions were determined. The incorporated kenaf fiber improved the mechanical and thermal properties of CDA. In the case of the composites containing 30 wt% kenaf fibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The removal of these compounds may have caused changes in the structure of the fibers. As a result, the reordering of the cellulose fibers and, because of that, the reduction in the surface volume may have increased the density …”
Section: Resultsmentioning
confidence: 99%
“…The removal of these compounds may have caused changes in the structure of the fibers. As a result, the reordering of the cellulose fibers and, because of that, the reduction in the surface volume may have increased the density …”
Section: Resultsmentioning
confidence: 99%
“…This increased interfacial adhesion through reduced fiber size (diameter) could permit more of the fiber to occupy a lesser volume. Thus, the overall bulk density of the composites based on the treated fibers could, therefore, be higher than those of the composites based on untreated fibers . We also found that the PSTFCs possessed higher densities than the PUTFCs.…”
Section: Resultsmentioning
confidence: 68%
“…This might have led to some structural modifications within the fiber and favored the crystalline cellulose, causing it to rearrange in a more ordered structural manner. The reordering could, therefore, increase the bulk density by reducing the surface volume . As for the lesser density of the STFs compared to the UTFs, the reason for this could be associated with some direct condensation reaction; this might have occurred between the silane (PDMS) and cellulose OH groups of the fiber, as reported elsewhere for silanized jute fibers .…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Kenaf fiber sized with poly(vinyl alcohol) was used to reinforce CDA, resulting in improved mechanical and thermal properties of CDA. Moreover, the tensile strength and elastic modulus of the composites increased by nearly two and three times, respectively, when the kenaf fiber content was 30 wt% [ 17 ]. Although the blending modification could improve the material’s properties, some problems, including poor compatibility, plasticizer precipitation, and degradation, still need urgent attention [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%